Outcomes of treatments for keratomalacia in dogs and cats: a systematic review of the published literature including non‐randomised controlled and non‐controlled studies. (2nd May 2021) - Hartley, C.
Abstract : Objectives: The aim of this review was to interrogate the evidence base for treatment of keratomalacia in dogs and cats, through examination of the applicable literature. Materials and Methods: Studies were screened for evidence to answer the following question Which of the treatment options for keratomalacia in dogs and cats offers the best chance of globe survival, the fastest time to resolution with globe survival, and the best visual outcome. The search utilised the PubMed (http://www.pubmed.gov/) and ISI Web of Science (http://wok.mimas.ac.uk/) databases. Databases were searched using the following terms: (keratomalacia OR corneal melt OR corneal malacia) AND (dog OR canine OR canid OR cat OR feline OR felid) AND (treatment OR outcome OR morbidity OR complications). Studies were assessed by one author (CH) and excluded if they related to less than three keratomalacia cases, experimental treatments, in vitro studies, or did not provide information regarding outcome. Studies were classified to a level of evidence according to the system described by the Oxford Centre for EvidenceBased Medicine. Results: Eighteen (18) studies were identified as providing information to answer the proposed question, one as level 3, 10 as level 4 and seven as level 5 evidence. Only one study compared two treatments, the remaining were prospective or retrospective case series of a single treatment intervention. Study design was highly variable with respect to population size, followup and outcome assessment, making direct comparison difficult, and metaanalysis was not applied. Clinical Significance: Overall, the evidence for improved outcome of one proposed treatment over another proposed treatment for keratomalacia in dogs and/or cats is very weak.